In vivo detection of scrapie cases from blood by infrared spectroscopy - Carmona, Pedro; Monzón, Marta; Monleón, Eva; Badiola, Juan José; Monreal, Jaime (Journal of General Virology, 2005)
In the present study, infrared spectroscopy was shown to be able to distinguish healthy and scrapie-infected animals by analysis of the white-cell membranous fraction from blood. Infrared spectroscopy was able to detect not only clinical cases, but also animals at a preclinical stage of the disease. These findings suggest this technique as an accurate in vivo diagnostic tool that could be applied to animal as well as human samples. In addition to possibly avoiding the slaughter of a huge number of animals with the socio-economic consequences that this poses, the test could be expected to become useful in the prevention of human transmission by blood transfusion.